Application of Steganography in Symmetric Key Cryptography with Genetic Algorithm (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Embedding maximum information in a stego-image with minimum change in its appearance has been a major concern in image-based steganography techniques. In this paper, utilizing Genetic algorithm (GA) we have built up a competent optimal robust steganography technique. The watermarks are implanted into the HL and LH frequency coefficients in bi-orthogonal wavelet transform (BWT). In order to get better the quality of stego image and robustness of the steganography we have to develop an optimization technique using a model to explore for the optimal locations. We examine the presentation of the suggested technique in terms of Peak signal to Noise ratio (PSNR) and Normalized correlation (NC). The proposed technique is the application of steganography for confidential transmission of symmetric key generated using Genetic algorithm (GA) that can accomplish a good imperceptibility and robustness of the image